PENDIDIKAN QADHA DAN QADAR DALAM AL-QURAN SURAT AL-HADID AYAT 22-23 MENURUT TAFSIR AL-AZHAR (STUDI KASUS ISPA PADA ANAK) - Rizal, Afri Eki; Charles, Charles (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Qadar is God's decree in determining or deciding the size of everything that happened before. Qadha and Qadar are the secrets of Allah, humans cannot know them before they happen. This research is library research, which is a series of activities related to methods of collecting library data, reading, taking notes, and processing research materials. Data collection techniques in this study through documentation. Based on the results of this study, it shows that surah Al-Hadid verses 22-23 explains that everything that happens on earth or oneself, as well as disasters occur by the will of Allah. The relationship between acute cough outbreaks in children with Qadha and Qadar QS Al-Hadid verse 22-23. That acute stone disease in children in Indonesia occurs by the will of Allah. If this is considered a problem, then in fact the problem is the result of human activity, because Allah always provides good for humans in accordance with the most merciful name.